Digital Storytelling in Political Marketing Communication Ganjar Pranowo and Anies Baswedan on Instagram Leading Up to the 2024 Presidential Election - Susilowati, Trisna; Rahmanto, Andre N.; Pawito (PT FORMOSA CENDEKIA GLOBAL, 2024)
The research has the objective to analyze the political marketing communication content on the Instagram accounts of Ganjar Pranowo and Anies Baswedan, as well as to analyze the aspect of digital storytelling. The researcher employed a visual content analysis method based on quantitative descriptive analysis of image types. The posts were categorized into 12 types of images. Additionally, we analyzed the digital storytelling elements in the uploads that featured the most image types. The outcomes indicate that Anies' digital storytelling strategy involves more interaction with his followers compared to Ganjar's strategy. The most frequently posted image type on the @aniesbaswedan account is campaign-related, which is suitable for political marketing communication efforts leading up to the 2024 presidential election. In contrast, the most frequently posted type of image on the @ganjar_pranowo account, background stories, is considered less appropriate for such purposes. Image types with themes suitable for the 2024 Presidential Election and presented in narrative form are likely to be more engaging, potentially encouraging followers to participate in exercising their voting rights